Dry matter intake and milk yield of cows grazing Xaraés palisadegrass under different management strategies - Vinícius Emanoel Carvalho; Saulo Alberto do Carmo Araújo; Danilo de Oliveira Alves; Carlos César dos Santos; Norberto Silva Rocha (Acta Scientiarum. Animal Sciences, 2019)
This study aimed to evaluate the intake and milk yield of crossbred cows (Holstein x Zebu), under two management strategies, based on 95% light interception and fixed days. Eight lactating cows with body weight of 466 kg (± 35 kg) and lactation stage of 137 days (± 107 days) were used, four animals were assigned to each treatment. Dry matter intake was estimated indirectly, using neutral detergent insoluble fiber as internal indicator and chromium oxide as external indicator. This was a completely randomized design, with four replications, two grazing strategies and three days of occupation. The animals under light management showed dry matter intake on the first day (11.42 kg) similar to the second day (9.57 kg), and this was similar to the third day (7.06 kg), but the intake on the first day was greater than on the third day. On the fixed days, intake did not differ between the first and second day (12.05 and 11.47 kg, respectively), and intake of the third day (6.70 kg) was lower than in the first two days. The dry matter intake in relation to the body weight of the animals presented similar results to the dry matter intake of forage in kilos, which can be explained by the small difference in weight between the mean of the groups. The individual milk yield showed a similar behavior among the grazing strategies for the days of occupation, which increased from the first to the second day (12.49 to 13.88 kg) and decreased from the second to the third day (12.20 kg). Grazing management strategies did not promote differences in the performance traits of lactating cows. The day of grazing during the period of occupation can be decisive for intake and production.